Views on Learning Difficulties in Basic Sciences by Mainland Chinese Students - Chan, Ken (Journal of International Students, 2021)
Science programs at Western higher education institutions are popular with mainland Chinese students. My teaching experience in Chinese classes suggests significant challenges for China-raised students in gaining deep appreciation and understanding of the principles of pure science, which differs from applied science in motivation and skills. The learning difficulties can be traced to students’ early education and cultural background. Science further communicates in a different style to other forms of English, adding complexity to writing and reading science texts. The information provided here could benefit future development of new course structures and teaching style in basic sciences, which is expected to generate a better appreciation of Western basic science philosophy by China-raised learners who in turn will gain a more rewarding learning experience.